Association of neutrophil to lymphocyte ratio with bone mineral density in post-menopausal women: a systematic review and meta-analysis - Maryam Salimi; Monireh Khanzadeh; Seyed Ali Nabipoorashrafi; Seyed Arsalan Seyedi; Shirin Yaghoobpoor; Jean-Michel Brismée; Brandon Lucke-Wold; Mehrnoosh Ebadi; Arshin Ghaedi; Varun Singh Kumar; Peyman Mirghaderi; Hamid Rabie; et al. (BMC, 2024)
Abstract Background We conducted a systematic review and meta-analysis to compare the neutrophil lymphocyte ratio (NLR) levels between women with post-menopausal osteopenia or osteoporosis to those with normal bone mineral density (BMD). Methods We used Web of Science, PubMed, and Scopus to conduct a systematic search for relevant publications published before June 19, 2022, only in English language. We reported standardized mean difference (SMD) with a 95% confidence interval (CI). Because a significant level of heterogeneity was found, we used the random-effects model to calculate pooled effects. We used the Newcastle-Ottawa scale for quality assessment. Results Overall, eight articles were included in the analysis. Post-menopausal women with osteoporosis had elevated levels of NLR compared to those without osteoporosis (SMD = 1.03, 95% CI = 0.18 to 1.88, p = 0.017, I2 = 98%). In addition, there was no difference between post-menopausal women with osteopenia and those without osteopenia in neutrophil lymphocyte ratio (NLR) levels (SMD = 0.58, 95% CI=-0.08 to 1.25, p = 0.085, I2 = 96.8%). However, there was no difference between post-menopausal women with osteoporosis and those with osteopenia in NLR levels (SMD = 0.75, 95% CI=-0.01 to 1.51, p = 0.05, I2 = 97.5%, random-effect model). Conclusion The results of this study point to NLR as a potential biomarker that may be easily introduced into clinical settings to help predict and prevent post-menopausal osteoporosis.